Pengaruh Persepsi Nilai, Persepsi Pengetahuan Lingkungan dan Sikap Terhadap Produk Hijau pada Niat Beli Hijau Konsumen Air Mineral Ades di Daerah Istimewa Yogyakarta - Nonik Kusuma Ningrum; Ambar Lukitaningsih; Intan Herdiana Larasati (Universitas Batanghari Jambi, 2022)
This study aims to explain the extent of the influence of Perceived Value, Perceived Environmental Knowledge Attitudes towards Green Products on Green Purchase Intentions of Ades Mineral Water Consumers in the Special Region of Yogyakarta. This study uses four variables, namely Perceived Value, Perceived Environmental Knowledge, Attitude towards Green Products as the independent variable and Green Purchase Intention as the dependent variable. The population that is taken in this study are those who buy Ades mineral water products at least once. The sampling method used Accidental Sampling and data collection using a questionnaire. The results showed that partially perceived value had a positive and significant effect on Green Purchase Intention, Perceived Environmental Knowledge did not have a positive and significant effect on Green Purchase Intention, and Attitudes towards Green Products had a positive and significant effect on Green Purchase Intention.